Developing an Interactive E-Module for Hadith Science Using Canva: A Design-Based Approach for Islamic Senior High School - Assalam, Gholib; Fatimah, Meti; Khoir, Mulyanto Abdullah; Nawaffani, Muhammad Mahsya (Abjadia : International Journal of Education, 2025)
This study aims to develop a Canva-based Interactive E-Module for Hadith Science to improve the quality of learning media for grade XI students of MA Al-Mukmin Ngruki. The study used a research and development (R&D) approach with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. The needs analysis showed that most students had difficulty understanding abstract concepts such as sanad, matan, and hadith classification and preferred interactive digital learning media. The design and development stage resulted in a module that integrates text, visualisations, diagrams, interactive quizzes, and video links according to multimedia learning principles. Validation by material and media experts obtained an average score of 4.45 (89%) and 4.35 (87%), and was declared very feasible. Implementation on 30 students as trial participants obtained a score of 4.32 (86%), indicating the module is effective in facilitating understanding, increasing motivation, and active involvement of students. Formative evaluation included revisions to the glossary, typography, and examples of hadith. The results of the study prove that the Canva-based interactive E-Module is able to be an innovative, interesting, and effective learning medium in supporting the understanding of Hadith Science for the younger generation.